Fermions, Gauge Bosons and Higgs Masses in the 3-3-1-1 Model with Charged Lepton - Si, Dang Trung; Thanh Phong, Nguyen; Nha, Nguyen Hua Thanh (VNU Journal of Science: Mathematics - Physics, 2021)
A new version of 3-3-1-1 model proposed can solve the Landau pole problem of the previous versions. The masses of fermions are calculated in detail where the masses of active neutrinos are generated through the seesaw mechanism. All the Higgs bosons and gauge bosons as well as their masses are identified and calculated.